Analysis of the utilization of groundcherry (Physalis angulata L.) by the community around the Cibodas Resort Gunung Gede Pangrango National Park - Ritawati, Alvionita; Zuhud, Ervizal AM; Hidayati, Syafitri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Groundcherry (Physalis angulata) is a medicinal plant originating from the Cibodas Resort forest, Gunung Gede Pangrango National Park. This study aimed to identify the actual potential of cecal plants and analyze perceptions, motivations, and perceptions of the impact of their utilization by the community around Cibodas Resort MGPNP. Research was carried out from September to November 2021, in Cibodas Resort MGPNP and Cimacan Village. The total number of groundcherrys found at an altitude of 1,000–1,600 masl is 148. Results of the Hawaii Pacific Weed Risk Assessment (HPWRA) for groundcherry are 20, which means they are high risk of becoming invasive in the area. The dominant characteristic of the Cimacan Village community is married to the last high school education level who works as an entrepreneur. The highest intensity utilization of the groundcherry is as an ingredient for food or drink consumption. Motivation of the community using groundcherry plants is same for religion, education, ecology, culture, recreation and society. Perceptions of impact of using groundcherry plants are uncertain to economic, social and cultural impacts. Perceptions of the ecological impact are considered disagreed by the surrounding community. Utilization by a community using a cultivation approach can be a solution to the high risk of invasiveness of groundcherry plants.